PENGARUH ASAM STEARAT TERHADAP SIFAT KETEGUHAN PATAH/MODULUS OF RUPTURE PAPAN PARTIKEL TERMOPLASTIK BEKAS BERPENGISI TEMPURUNG KELAPA - Muh. Hendra S Ginting, Rosdanelli Hasibuan (Jurnal Teknik Kimia USU, 2014)
The utilization of former thermoplastic and coconut shell as particle board is one way to reduce plastic waste packaging, the ratio of the former as a thermoplastic matrix and coconut shells as fillers 60:40. Purpose of this study was to determine the effect of stearic acid on properties of modulus of rupture former thermoplastic particle board filler of coconut shell. Method of shell particle board manufacturing using the extruder, starting with the modification of coconut shell particles (size 80 mesh) with stearic acid (0 g, 3 g, 6 g and 9 g in 60 ml of ethanol ) and then dried in an oven at a temperature 70oC . Matrix and coconut shell ( 60:40 ) mixed in the extruder and then printed with hot press at a temperature of 170oC, until forming particle board with a size of 200 mm x 200 mm x 10 mm. Particle board analyzed the modulus of rupture in accordance with SNI 03-2105-2006. The results showed an increase in modulus of rupture properties. The modulus of rupture is 37.402 MPa greatest.